Network disruption detected in GD (GD) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in GD. Data sourced from IODA.
Network Disruption Incident ID: GD-2026-0001. Severity: critical. Confidence: 67%